2004
DOI: 10.1021/jp047947y
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of 1,8-Bis(dimethylamino)naphthalene in Solution:  Internal Charge Transfer with a Twist

Abstract: The photophysical properties of the excited states of 1,8-(bisdimethylamino)naphthalene have been investigated by a combination of experimental spectroscopic methods and quantum chemical calculations. The experiments show that vertical excitation occurs to an 1La-type state from which internal conversion occurs to a state with dominant internal charge-transfer character. This character gives rise to weak emissive properties, a strong solvent dependence of the emission, and transient absorption spectra that car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…This spectrum agrees very well with the nanosecond transient absorption spectrum determined for the emissive state of DMAN in n-hexane. 10 Moreover, the decay times determined here by femtosecond transient absorption are in good agreement with those obtained by picosecond time-correlated single-photoncounting measurements. We therefore conclude that the species associated with the SADS µ is the relaxed lπ* state.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This spectrum agrees very well with the nanosecond transient absorption spectrum determined for the emissive state of DMAN in n-hexane. 10 Moreover, the decay times determined here by femtosecond transient absorption are in good agreement with those obtained by picosecond time-correlated single-photoncounting measurements. We therefore conclude that the species associated with the SADS µ is the relaxed lπ* state.…”
Section: Resultssupporting
confidence: 85%
“…10,13 The same calculations showed that the Stokes shift for the emission from the 1 L a state should be considerably smaller than that for Dashed lines indicate the fit described in the text. Note that the time axis is linear from -1 ps to 1 ps relative to the maximum of the IRF, and logarithmic afterward.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The steady-state fluorescence spectra of 1 (Figure a, curves 1′–4′) exhibited a very weak solvatochromism with noticeable Stokes shifts (∼1000–1300 cm –1 ), even in nonpolar TOL (see Table ). These peculiarities in the spectral behavior of 1 are evidence of small changes in the permanent dipole moment of 1 , Δ μ 01 , under electronic excitation S 0 → S 1 , and large rearrangement of the optimized geometry in the S 1 state (S 0 and S 1 are the ground and first excited electronic states, respectively). As follows from the 3D fluorescence emission map of 1 (Figure b), all steady-state fluorescence spectra were independent of excitation wavelength, λ ex , and in good correspondence with Kasha’s rule …”
Section: Resultsmentioning
confidence: 99%
“…29 The steady-state fluorescence spectra of 1 and 2 (Figures 1a and 1b, curves 1′ and 2′) also exhibited weak solvatochromic behavior and relatively large Stokes shifts of ∼4000−4800 cm −1 , even in low polarity solvents, which indicates sufficiently large changes in the optimized molecular geometry upon electronic excitation from S 0 → S 1 (S 0 and S 1 are the ground and first excited electronic states, respectively). 48 The corrected excitation spectra of 1 and 2 for the observed wavelength, λ obs , in the spectral range of ∼550−750 nm ( Figure 2, curve 2) nicely overlapped with the corresponding 1PA spectra (curve 1), which is evidence of only one fluorescence species in this spectral range. It is interesting to mention that three-dimensional (3D) fluorescence spectra of 2 ( Figure 3) reveal an additional weak fluorescence band with a maximum at ∼425 nm.…”
Section: Resultsmentioning
confidence: 70%